Caracterización del genoma apicoplástico de Plasmodium sp. causante de malaria aviar cuenca alta río Itaya Loreto Perú - Apuela Guerra, Llaqueli (2023)
The present study was carried out between 2020 and 2021 in the Concession area of the Scientific University of Peru-UCP, in the upper basin of the Itaya river, in its Biotechnology and Bioenergetics laboratories and the Natural Resources Research Center of the Peruvian Amazon – CIRNA (UNAP) respectively. It should be noted that research on avian malaria indicates that some species of apicomplex parasites that cause this disease are invasive and are responsible for the loss of bird diversity worldwide. Control of these parasites has been limited, partly due to the lack of basic knowledge at the molecular level, since the genomic resources of these parasites are very limited. To help fill these knowledge gaps, the main objective of this research was to characterize the apicoplastic genome of Plasmodium sp. cause of avian malaria in the upper basin of the river Itaya Loreto Peru. To do this, genomic DNA was purified from blood samples of infected birds. Subsequently, the DNA libraries were prepared and sequenced with state-of-the-art technology (next seq 550). The obtained sequences were assembled and functionally annotated with several bioinformatic tools to obtain the apicoplastic genome. The results showed that the assembled and annotated genome is circular in shape, compact, 29.36 kb in size, and has a high A+T content (86.9%). Likewise, 56 genes with a typical distribution of apicomplexes of the genus Plasmodium have been identified, most of them participate in the synthesis of RNA and proteins. Finally, according to phylogenetic analyses, the parasite studied belongs to the Plasmodium relictum species, one of the main causes of avian malaria in the Peruvian Amazon and several regions of Peru. In conclusion, it has been possible to assemble and functionally annotate the apicholastic genome of an apicomplex parasite of the genus Plasmodium that causes malaria in birds from the upper Itaya river basin.